Genetically-Modified Hematopoietic Stem Cells and their Progeny for Widespread and Efficient Protein Delivery to Diseased Sites: The Case of Lysosomal Storage Disorders - Biffi, Alessandra (Current Gene Therapy, 2012)
Efficient therapeutic protein delivery is a challenging task in several disease contexts and particularly when the CNS is concerned. Different approaches for brain-directed delivery have been thus far investigated, including direct injection of molecules or of their coding information carried by dedicated vector systems within the brain parenchyma or in the ventricular space, intravenous systemic administration of molecules/vectors modified to target and cross the blood-brainbarrier, and exploitation of allogeneic and/or autologous and genetically modified cells as vehicles for the therapeutic of interest. Among these, we here review one of the most promising approaches based on hematopoietic stem cells, taking advantage of lysosomal storage disorders as representative disease setting.
Keywords: protein delivery